A comprehensive electromagnetic simulation model for switched reluctance motor operating under multiphase excitation (Engineering Review, 2019)
In the present paper, a comprehensive electromagnetic simulation model based on finite element method (FEM) is introduced for the switched reluctance motor (SRM) by which important electromagnetic characteristics are predicted for the multiphase excitation mode. The inputs of the model are the design data and control parameters and it considers different arrangements of the phase winding connections. The simulation model is developed totally in ANSYS parametric design language (APDL) as a parametric model and it can be used easily for different types of the SRM. Carrying out 2D finite element transient analysis in the simulation model, flux density waveforms within the motor are predicted and a procedure is developed for core loss determination of the SRM operating under multiphase excitation. Applying the introduced simulation model to an 8/6 SRM, simulation results are presented for operation with simultaneous two- phase excitation.